Mechanical Modeling of Frozen Coarse-Grained Materials Incorporating Microscale Investigation - Shan-Zhen Li; Liang Tang; Shuang Tian; Xian-Zhang Ling; Yang-Sheng Ye; De-Gou Cai (Advances in Materials Science and Engineering)
In the cold regions of China, coarse-grained materials are frequently encountered or used as backfilling materials in infrastructure construction, such as dams, highways, railways, and mineral engineering structures. Effects of confining pressure (0.2, 0.5, and 1 MPa) and frozen temperature (−2, −5, −10, and −15°C) on the stress-strain response and elastic modulus were investigated using triaxial compression tests. Moreover, the microscale structures of a coarse-grained material were obtained by X-ray computed tomography. The coarse-grained material specimens exhibited strain-softening and significant dilatancy behaviors during shearing. A modified model considering microstructures of the material was proposed to describe these phenomena. The predicted values coincided well with the experimental results obtained in this study and other literatures. The sensitivity analysis of parameters indicated that the model can simulate the initial hardening and post-peak strain-softening behavior of soils. And the transition of volume strain from contraction to dilatancy can also be described using this model. The results obtained in this study can provide a helpful reference for the analysis of frozen coarse-grained materials in geotechnical engineering.